Evaluasi Keterlaksanaan Gerakan Literasi Sekolah dalam Persiapan Assesemen Kompetensi Minimum pada Program Kampus Mengajar 2 di SDN Sugihrejo 03 - Astutik, Lia; Purnamasari, Iin; Rofian, Rofian (Pena Edukasia, 2022)
The low interest in reading in elementary school students at this time so that it is necessary to get used to reading 15 minutes every day before learning begins. The School Literacy Movement plays an important role in institutions because reading activities can provoke students to read so that it will increase students' reading interest in each school. This research method uses a descriptive qualitative approach. Data were obtained from carrying out observations or observations, interviews with the Principal and 6 Class Teachers and filling out an open questionnaire. Based on research, the implementation of the School Literacy Movement has been going well, although not optimally, and there are differences and similarities that have been prepared or strategies from classroom teachers to increase students' reading interest. The method used by low grade and high grade teachers. The impact of the School Literacy Movement experienced by students during the habit of reading 15 minutes before learning begins. facilities and infrastructure in schools to support the School Literacy Movement program, namely a library equipped with a reading corner and interesting illustrated reading books.